HOW ACCURATE GOOGLE TRANSLATE IN TRANSLATING JAVANESE HUMOUR “MBAH MINTO VS BOCIL” INTO ENGLISH VERSION - Ika Oktaria Cahyaningrum; Didit Kurniadi; Budi Purnomo (Acceleration: Multidisciplinary Research Journal, 2023)
Google translate as a translation machine provides various conveniences for its users, approximately 109 languages are provided on google translate. The latest update of this application is the Java language. In this study, the researcher took the research object for the data from Javanese humor entitled "Mbah Minto vs Bocil" translated into English using Google Translate. This research includes qualitative descriptive research, which describes or generalizes data and facts and is presented in the form of a concrete description, detailed data. Mbah Minto is one of the most popular Javanese humors belongs to Ucup Klaten YouTube channel in 2022. This online translation application is very helpful, especially for translation users. Previous studies have discussed the quality of the translation produced by Google Translate which will be more acceptable and more accurate at the sentence level, but not at the verse or lyrics level with the use of words that mostly use figures of speech so that it will greatly affect the results of the translation produced by Google Translate. The data source in this study is the sort movie taken from YouTube channel produced by Ucup Klaten, while for this research data is the script in the Javanese conversation on the short movie. In translating the text, the important thing is the process to maintain the equivalence between source text to the target text. Translation methods that emphasize more on external factors can be used to overcome this problem, but this can lead to other problems, one of which is the equivalence of meaning.